Transient Behaviour of Superconducting Magnet Systems of Fusion Reactor ITER during Safety Discharge. (28th December 2008) - Miri, A. M.; Fink, S.; Fietz, W. H.
Abstract : To investigate the transient behaviour of the toroidal and poloidal field coils magnet systems of the International Thermonuclear Experimental Reactor during safety discharge, network models with lumped elements are established. Frequency-dependant values of the network elements, that is, inductances and resistances are calculated with the finite element method. That way, overvoltages can be determined. According to these overvoltages, the insulation coordination of coils has to be selected.